Contribution factors to medication error among pharmacy professional in Hospital Selayang, Selangor - Zulkurnain, Ezza Izzati; Ramli, Nur Syazwani (2018)
Pharmacy professional should take serious about medication error since it can give harmful implication towards patient and the pharmacy professional their selves. The factor that most contribute to medication error in Hospital Selayang has been observed and studied. There are many factors that can lead to medication errors, as example, heavy workload, look alike sound alike (LASA), illegible handwriting, personal problem, lack of therapeutic training, and lack of knowledge of medication. Thus to collect the data, we have distributed questionnaires among the pharmacy professional in Hospital Selayang which involving pharmacists, pharmacy technicians and also pharmacy students. The focus of this study is to identify the most factors that lead the pharmacy professionals to make medication error. Most of the respondents have choose heavy workload as the main factor that contribute to medication error. Heavy workload which is they are having a lot of work that they need to handle, increasing number of patients, or does not enough workers in certain pharmacy department. Beside that, we relate their timeframe experiences of working and the frequency of medication error that they have made. We key in the data that we collect from the filled questionnaires in the SPSS (Statistical Package for the Social Sciences) version 16.0 to get the exact result that have been interpreted into table and graph form. From the result, pharmacies professional that have longer experiences in working are rarely make medication errors compare to pharmacy professional who have short timeframe of experiences. In this study, the contribution factors to the medication error is depend on which department they are attached. By finding the factors, it is easier to find a way and solution to reduce medication error from occurs such as, counter checking the medication vibefore it reach the patients. As the conclusion, heavy workload is one of the main factors that can lead pharmacy professional to make medication error.